THE ANALYSIS ON FACTORS AFFECTING INCOME LEVEL OF FISHERMAN (A CASE STUDY ON FISHERMAN IN THE COASTAL AREAS OF KRANJI VILLAGE OF PACIRAN SUBDISTRICT IN LAMONGAN REGENCY) - Anshori Tsani SE (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
This study aims to identify the simultaneous and partial effects of capital, age, work hours, experience, selling price, and catches on the income of fishermen in the Kranji village of Paciran subdistrict in Lamongan regency. The variables of this study, i.e. capital, age, work hours, experience of selling prices, and catches, were examined thoroughly using observation, interview, and documentation. The population of this study are 730 fishermen, from which 90 people were selected as the sample. The data was analyzed using multiple linear regression. This study finds that capital, age, work hours, experience, selling price, and catches simultaneously have significant influences on the income of fishermen in Kranji Village of Paciran subdistrict in Lamongan regency. Furthermore, capital, age and work hours partially don not have any significant influence the income of fishermen in Kranji village of Paciran subdistrict in Lamongan regency. While the experience, selling price, and catch variables partially have a significant influence on the income of fishermen in Kranji village, Paciran subdistrict, Lamongan regency. In addition, selling price is dominant in influencing the income of fishermen in Kranji village of Paciran subdistrict in Lamongan regency at 29.1%. Keywords: capital, age, work hours, experience, selling price, catches